Design cost and scaling model of superconducting wind turbine generator for electricity generation - Hamid N.A.; Suparin M.F.; Gokila T.; Ewe L.S. (Trans Tech Publications Ltd, 2023)
This paper reports on the design cost and scaling model of a small scale superconducting wind turbine generator, where the levelized cost of energy (COE) was calculated. The proposed design of the wind turbine is based on the vertical axis wind turbine (VAWT) type that drives the superconducting generator. VAWT was chosen due to its ability to operate under low wind speed. Wind turbine using superconducting generator was proposed since it is able to enhance magnetic flux within the stator of the generator and consequently improve the performance of the generator. Once the design has been accomplished, all the cost of parts and components must be accounted and contributes to the overall cost of generating electrical energy from the superconducting wind turbine generator. The cost elements include the initial capital cost (ICC), balance of station (BOS), operation and maintenance (O&M), levelized replacement cost (LRC) and annual energy production (AEP). The calculated levelized COE shows that the cost of generating electricity using superconducting wind turbine generator is lower than generating electricity from conventional sources. © (2014) Trans Tech Publications, Switzerland.